2008
DOI: 10.1038/cdd.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of heat-shock protein 90β isoform (HSP90β) with cellular inhibitor of apoptosis 1 (c-IAP1) is required for cell differentiation

Abstract: Members of the inhibitor of apoptosis protein (IAP) family have demonstrated functions in cell death, cell signalling, cell migration and mitosis. Several of them are E3 enzymes in the ubiquitination of proteins that leads to their degradation by the proteosomal machinery. We previously reported that one of them, cellular inhibitor of apoptosis protein-1 (c-IAP1), migrated from the nucleus to the surface of the Golgi apparatus in cells undergoing differentiation. Here, we show that c-IAP1 is a client protein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…8,12,13 We have previously shown that cIAP1 is required for optimal differentiation of monocytes into macrophages. 25 We show here that cIAP1 is one of the E3 ligases involved in the proteasome-dependent degradation of TRAF2 along this differentiation process. Because the effect of cIAP1 inhibition on differentiation-associated TRAF2 down-regulation was only partial, we cannot rule out a function for TRAF2 itself, Siah2, or other E3 in this event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12,13 We have previously shown that cIAP1 is required for optimal differentiation of monocytes into macrophages. 25 We show here that cIAP1 is one of the E3 ligases involved in the proteasome-dependent degradation of TRAF2 along this differentiation process. Because the effect of cIAP1 inhibition on differentiation-associated TRAF2 down-regulation was only partial, we cannot rule out a function for TRAF2 itself, Siah2, or other E3 in this event.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,[22][23][24] We have previously shown that cIAP1 was required for macrophage differentiation. 25 We have also shown that cIAP1 migrated from the nucleus to the cytoplasm to concentrate at the surface of the Golgi apparatus in monocytes undergoing differentiation into macrophages. 26 However, the role of cIAP1 and the functional significance of its differentiation-associated redistribution remained unknown.…”
Section: Introductionmentioning
confidence: 94%
“…More over, the expression and stability of IAPs are regulated by molecular chaperone such as heatshock proteins. 72,73 The molecular mechanisms of caspase regulation by BIRC4/XIAP have been extensively investigated in biochemical and structural studies (reviewed in ref. 11).…”
Section: Iaps: Apoptosis Regulatorsmentioning
confidence: 99%
“…Our current data with ML-IAP also suggest that IAPs synergize with the chaperone machinery to regulate C-RAF levels. In fact, cIAP1 has been shown to be associated with Hsp90 during cellular differentiation (46). Further, silencing of CHIP expression has also led to an increase in C-RAF levels in these melanoma cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 85%